Izgubljeni potenciali kreativne urbane regeneracije - Uršič, Matjaž (Urbani izziv, 2021)
In the transition that saw intense spatial and economic changes in Slovenia, urban creative activities were often regarded as an important development factor allowing the reurbanization and revitalization of several former industrial areas. These were generally relatively spontaneous unplanned processes to spatially and economically develop degraded areas where, following the bottom-up principle, various creative individuals and groups gradually revitalized these areas. This article analyses the role of creative activities in breathing life into degraded areas by looking at the development of soft (social) factors in the form of social networks. It highlights the problem of local authorities and state institutional actors' non-perception of, inappropriate approach to, or insufficient con-sideration of creative social networks in developing these spaces. Drawing on semi-structured interviews, the case of the former tobacco factory is presented as an example of the accumulation of social capital linked to social networks, within which the area's new economic and spatial restructuring is perceived to be an unnecessary element of the renovation.
Keywords: creative activities; degraded areas; degradirana območja; Družbena omrežja; kreativne dejavnosti; Revitalizacija mest; Revitalization of cities; Social networks; tobacco factory; Tobačna tovarna; Urban sociology; Urbana sociologija